Potential of the extract from the nut of Areca catechu to control mango anthracnose - Ahmad Rusdan, Aizad Izha; Kadir, Jugah; Tengku Muda Mohamed, Mahmud; Ee, Gwendoline Cheng Lian (Universiti Putra Malaysia Press, 2015)
Anthracnose is a common disease that attacks mangoes in many regions, including Malaysia. In this study, extracts from the nuts of Areca catechu were tested for their antifungal activities in controlling the disease. Antifungal screening tests were done using six extracts i.e. hexane, chloroform and methanol from ripe and unripe nuts of A. catechu to determine their ability to inhibit mycelium growth and spore germination of Colletotrichum gloeosporioides isolated from mango. Of the six extracts, the chloroform extract from unripe nuts at a concentration of 10 mg/mL showed the best antifungal activity, inhibiting about 52% of mycelium growth and 100% of spore germination. Thus, this particular extract was selected to treat the fruit against anthracnose in two different ways, namely, by dipping them in the extract solution at 27o C for one hour (normal dip) and also at 52o C for five minutes (hot dip). Meanwhile, control and benomyl solutions (each applied in both dipping methods) were used as comparisons. The test proved that the treatment using the extract reduced 34% of disease infection and 27% of disease rate from the control. However, the treatment using benomyl was slightly effective compared to using the extract, reducing around 47% of disease infection and 38% of disease rate from the control. Hence, results from test also proved that the treatment applied at 52o C reducing 51% of disease infection and 35% of disease rate than those conducted at 27o C. Compound screening tests on the chloroform extract of the unripe nuts revealed that the extract contained alkaloids and phenolics. Many previous studies have proven that alkaloids and phenolics from various plants could cause antifungal activities and these substances might be responsible for controlling anthracnose development in the study done.